25-Hydroxyvitamin D Serum Levels and Endometriosis: Results of a Case–Control Study. (February 2019) - Buggio, Laura; Somigliana, Edgardo; Pizzi, Mara Nicoletta; Dridi, Dhouha; Roncella, Elena; Vercellini, Paolo
The immunomodulatory, anti-inflammatory, and antiproliferative properties of vitamin D have laid the basis for a possible function of this prohormone in the pathogenesis of endometriosis. The aim of this case–control study was to investigate vitamin D status, by measuring 25-hydroxyvitamin D [25(OH)D] serum levels, in women with and without endometriosis. Only Italian women of Caucasian origin aged between 18 and 45 years were deemed eligible. Enrollment was limited to the period October to May. Cases and controls were matched for month of recruitment and secondarily for age and parity. Overall, 434 women were enrolled (endometriosis n = 217; controls n = 217). The group of cases included 127 women with ovarian endometrioma and 90 patients with deep endometriosis. Mean (standard deviation) levels of 25(OH)D in women with and without endometriosis were 17.9 (7.0) ng/mL and 18.4 (7.6) ng/mL, respectively ( P = .46). Analyzing the two endometriosis subgroups separately, no statistically significant differences emerged (18.7 [7.4] ng/mL in deep endometriosis group vs 17.3 [6.6] ng/mL in women with ovarian endometrioma; P = .14). Comparing the subgroup of women with deep endometriosis with paired controls, no differences occurred (18.7 [7.4] ng/mL vs 18.5 [7.7] ng/mL, P = .80). Similar data emerged when performing the same analysis for ovarian endometriomas (17.4 [6.6] ng/mL vs 18.3 [7.6] ng/mL, P = .23). The results of the present case–control study do not support an association between serum vitamin D levels and different phenotypes of endometriosis.